BENTUK DAN FUNGSI GERABAH KAWASAN DANAU SENTANI - Hari Suroto (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2011)
Based on the research done, earthenware is found in Sentani Lake. The earthenware which is found in pieces, is later concluded as pot and crock after the reconstruction was made. The size of the pot is small and thin while the crock is big and thick. The function of the earthenware can be analyse from the shape and link it to the other earthenware. After analysing them, it is concluded that pot was used for cooking, while crock was used for keeping food and water.